Characterization of 14 tomato (Lycopersicon esculentum Mill.) genotypes grown under greenhouse conditions in Costa Rica - Monge-Pérez, José Eladio (2014)
Fourteen tomato genotypes grown under greenhouse conditions were characterized, both at qualitative and quantitative levels. Data show a wide variability between genotypes, and this information is useful for growers to choose the best variety for their particular market purposes. Some ‘cherry’ and ‘grape’ tomato genotypes show high soluble solid contents; these varieties could be good choices for consumers that demand high quality tomatoes.